Physiological effect on growth, yield and storage qualities of onion (Allium cepa) - PRAMANICK, KALLOL KUMAR; SINGH, NARENDRA; NETRAPAL, NETRAPAL (The Indian Journal of Agricultural Sciences, 2013)
An investigation was carried out with 7 varieties/lines of onion (Allium cepa L.) to select superior variety/line forits yield and storage qualities. The differences observed between the varieties/lines were highly significant for all thecharacters. ’Pusa Red’ found to be best for yield followed by ’81 126’. ’SI 126’ was the best for total soluble solids, drymatter (%) and ascorbic acid content which could be effectively used for table, dehydration as well as for storagepurposes. ’Pusa Red’ was the best variety regarding yield and storage followed by "SI 126’. ’Early Grano’ was the leastpungent and ’N 53’ and ’SI 106’ were the next in succession. ’Early Grano’ was the poorest in keeping quality followedby ’SI 131’. Studies on growth rate also indicated that the varieties/lines differed significantly in their growth rhythm.Fresh leaf weight increased gradually up to 90 days after transplanting but fresh bulb weight. increased graduallythere after indicating it to be critical phase where separation between the active vegetative and maturation phase. Harvestindex confirmed early maturing status of ’Early Grano’ which entered into its maturation phase earlier but it wasreverse in case oflongest duration variety,’Pusa Red’.’Early Grano’ was more fleshy and mild hence could be used ,forsalad purposes. ’Pusa Red’ and ’SI 126’ found to be best for yield and storage quality. ’Pusa Red’ was of the longest,whereas ’Early Grano’ was the shortest duration variety.